Collection of Contemporary Christian Art in the Yenisei Historical and Architectural Museum-Reserve named after A. I. Kytmanov: History of Formation and Development Prospects - V. V. Barashkov (Концепт: философия, религия, культура, 2023)
The subject of this study is the works of modern Christian painting, graphics and sculpture on the example of the collection that became part of the Yenisei Museum-Reserve in 2021. The relevance lies in the clarification of a number of theoretical aspects of the dialogue between contemporary art and religion on the example of the interaction of the priest Andrei Yurevich with Siberian artists. The novelty lies in the description of the socio-cultural context of the formation of the collection in the 2000s. In order to identify the main trends in Christian art, the typology method was applied, and an interview was also conducted with the founder of the collection, priest Andrei Yurevich, and with art historian M. V. Moskalyuk, the original works in the Yenisei Museum-Reserve were examined. The theoretical results include the reconstruction of the history of the formation of the collection, the stages of its development (from the private initiative of the priest to the parish museum, later to the diocesan museum and, finally, inclusion in the state museum). Based on the analysis of individual works from the collection, a typology of the main trends in contemporary Christian art is developed. In the last part of the article, various options for updating the considered works in the exhibition activities of the Yenisei Museum-Reserve were developed. In particular, the special significance of paintings that reveal the local history of Eastern Siberia is shown, the possibility of a comparative demonstration of the collection's works with the works of artists of the second half of the 19th – early 20th centuries is assessed. In conclusion, the regularity of the collection entering the state museum is emphasized in connection with the new approach to the definition of the concept of museum, which involves working with different communities, including believers.